The form, field and order of anti-extractivist protests in Mozambique - Blanes, Ruy Llera (CIES-Iscte Monthly Seminar in Social Movements and Political Action, 2024)
In this seminar I propose to map the dynamics of social mobilization – from NGOs to peasant associations, communal protests and platforms of those affected – around new extractive projects in Mozambique, in the context of the current debates on the energy transition. Through examples taken from field research in Maputo, Pemba and Balama, I will seek to explore how transnational movements intersect with local claims in the context of the deployment of infrastructure related to extractive mega-projects in Cabo Delgado, namely Natural Gas and Graphite. I will propose that these intersections form a "field" with concrete potentialities and limitations in terms of identifying and responding to the problems of local communities.